Written on the heart the case for natural law - Budziszewski, J., 1952- (Downers Grove, Ill. : InterVarsity Press, 1997)
With uninterrupted clarity, frequent eloquence and occasional humor, J. Budziszewski presents and defends the natural-law tradition in what is at once a primer for students and a vigorous argument for scholars. Written on the Heart expounds the work of the leading architects of theory on natural law, including Aristotle, Thomas Aquinas and John Locke. It also takes up contemporary philosophy, theology and political science, colorfully running against the intimidating tide of advanced pluralism that finds natural law so difficult to tolerate.
Aristotle. Politics & the human good ; Moral excellence & regime design ; Friendship, justice & the moral significance of law -- Thomas Aquinas. The grand design of law ; The law of nature & the law of man ; Human law & regime design -- John Locke. The state of nature & the social contract ; Two views of natural law ; Private property & revolution -- John Stuart Mill. The pleasure principle ; The problem with the pleasure principle ; Utility & justice -- Intermezzo : the art of teaching -- Written on the heart. A Christian appraisal of natural-law theory ; A reprise of the older thinkers ; A sampling of recent thinkers -- Appendix : elementary reasoning.
Includes bibliographical references (p. [241]-244) and index.
Description based on print version record.
Keywords: Natural law; Law -- Political aspects; Religion and law; LAW / Natural Law; Electronic books